Design and preliminary finite element analysis of planar rotary spring for BioApps RoMicP® ankle-foot prosthesis / Aufar Syehan - Aufar, Syehan (2022)
Series elastic actuator (SEA) is an excellent option for a powered ankle-foot prosthesis. However, to achieve the best actuator performance, the optimum stiffness of the planar rotary spring should be defined by using a dynamic model. The main objective of this study is to develop a planar rotary spring design with an optimum stiffness. Maraging 300 Alloy Steel or commercially known as Vascomax-300 was selected as the material of the planar rotary spring for the BioApps RoMicP®️ ankle-foot prosthesis. Furthermore, Archimedean spiral was chosen as the topological shape of the spring. The spring model was developed in an iterative method, where the width and thickness of the spring’ arm were the parameters to be modified until the spring model reached the optimum stiffness value. The definition of an optimum torsional spring stiffness is when the power required by the motor is minimum. Following the completion of the design advancement the reliability of the preliminary spring design was examined by using the Finite Element Method (FEM). Based on the simulation, the planar rotary spring model was able to withstand a maximum torque of 102.793 Nm. The spring rotation was 0.163 rad, corresponding to a torsional stiffness between 620 and 630 Nm/rad.